(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents a comprehensive comparative analysis of the linguistic units denoting reproach in English and Russian. It aims to explore the intricate ways in which reproach, a fundamental speech act in human communication, is expressed across these two distinct languages and cultures. Through a methodological blend of corpus analysis, literary review, and elicitation tasks, the study identifies and categorizes various forms of reproach found in both English and Russian. The results reveal a striking contrast in the expression of reproach in these languages, reflecting their respective cultural norms and communication styles. English reproach tends to employ indirect strategies and polite forms, whereas Russian reproach is characterized by its directness and explicitness. The discussion delves into the cultural implications of these findings, suggesting that the manner of expressing reproach is deeply rooted in societal values and communication etiquette. The study also examines the role of reproach in literary works, providing a rich context for understanding its application and perception in English and Russian literature. The article concludes by highlighting the importance of understanding linguistic nuances in reproach for effective cross-cultural communication and language learning. It emphasizes the need for further research in this area, particularly in the context of an increasingly interconnected global community. This comparative linguistic study contributes to the broader understanding of pragmatics, sociolinguistics, and intercultural communication, offering valuable insights for linguists, educators, translators, and intercultural communicators.